Greenhouse affect: the relationship between the sustainable design of schools and children’s environmental attitudes - Izadpanahi, Parisa; Elkadi, H.; Tucker, R. (Routledge, 2015)
This study aims to determine if primary school children’s environmental attitudes can be predicted by whether their school had been designed or adapted for sustainability. A New Ecological Paradigm (NEP) scale for children was adopted to measure attitudes, with supplementary questions added to align this scale to the Australian context of the study. In addition, the original adult NEP scale was used to determine relationships between children’s environmental attitudes, their School Design and their Parents’ and Teachers’ Environmental Attitudes. Data collected from grade 4, 5 and 6 primary school children, their parents and teachers were analysed via three multiple regressions. The results indicate that sustainable design in schools improves the environmental attitudes of children towards perceptibly green building features, such as solar panels, the use of recycled water, natural daylighting and outdoor classrooms including food-producing gardens.